2008
DOI: 10.1007/s10493-008-9171-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and thermotolerance of entomopathogenic fungi for the control of the scab mite, Psoroptes ovis

Abstract: Psoroptes ovis is responsible for a highly contagious skin condition, both in sheep and cattle. This parasite has a marked economical impact in the sheep and cattle industry. Biological control is considered as a realistic alternative to chemotherapeutic control. Laboratory experiments were carried out to evaluate the pathogenicity and the thermotolerance of twelve isolates of entomopathogenic fungi from four genera (Beauveria Vuillemin, Metarhizium Sorokin, Paecilomyces Bainier and Verticillium Nees). The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Supporting evidence for this comes from results that indicate that 33°C is too hot for the sporulation, growth and viability of B. bassiana [31]. Further evidence can be found in a series of laboratory studies that reported relatively rapid losses in fungal viability after exposure to heat and humidity [11,22,32,33] and from B. bassiana gene-knockout studies that linked thermotolerance to viability [34,35]. In concurrence with these findings, Scholte et al [18] found that the viability of M. anisopliae- treated cotton sheets decreased from 96% in suspension to 63% three weeks after application in Tanzania, whereas the viability of the conidia remaining in suspension did not change [18], as was found in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting evidence for this comes from results that indicate that 33°C is too hot for the sporulation, growth and viability of B. bassiana [31]. Further evidence can be found in a series of laboratory studies that reported relatively rapid losses in fungal viability after exposure to heat and humidity [11,22,32,33] and from B. bassiana gene-knockout studies that linked thermotolerance to viability [34,35]. In concurrence with these findings, Scholte et al [18] found that the viability of M. anisopliae- treated cotton sheets decreased from 96% in suspension to 63% three weeks after application in Tanzania, whereas the viability of the conidia remaining in suspension did not change [18], as was found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…When oil-formulated fungal conidia were applied to polyester netting and kept at 27°C, the viabilities of M. anisopliae and B. bassiana were significantly reduced both one day and again one week after application, although this may also have been due to the polyester netting substrate [11]. Lekimme et al [22] inoculated temperate and tropical strains of B. bassiana and M. anisopliae onto agar plates and held them at a range of temperatures to investigate thermotolerance. They found that at 35°C only one M. anisopliae strain and none of their B. bassiana strains grew [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of parasite killing and thermotolerance are of capital importance to allow the molds to carry out their entomopathogenic activity. These features depend on the selected fungal isolate [274]; B. bassiana was reported to show the optimal growth temperature between 25 • C and 28 • C [275], even if some isolates can grow at about 30 • C, with highly reduced activity and may not survive at 34 • C [276].…”
Section: Fungimentioning
confidence: 99%
“…Report cases of disease caused Psoroptes sp. the possum has not been published, one of a kind Psoroptes is Psoroptes cuniculi generally attacks on domesticated livestock such as rabbits (Acar et al, 2007;Kyung-Yeon & Oh-Deog, 2010), Psoroptes is the causative agent of dermatitis in cattle, sheep, goats, rabbits and turkey (Kurtdede et al, 2007;Lekimme et al, 2008). Type P. cuniculi attack on wildlife group Artiodactyls reported by Pederson et al (2007), whereas the incidence of deer in the United States reported by Schmith et al (1982).…”
Section: Introductionmentioning
confidence: 99%